Assessing a Consortium for a Multidisciplinary Subject. Issue 1 (2nd January 2021) - Phelps, Sue F.
Abstract: This paper reports on a study to assess the Orbis Cascade Alliance's print collection for material supporting the Black experience. It covers descriptions of general methods used for collection assessment as well as those used to assess the Alliance including Brief Tests, List Checking, and Comparison Studies. Each method is described with its strengths and weaknesses as well as their application to a consortium of libraries with Black experience being the subject matter of the material collected. These methods can be used for other multidisciplinary topics. Issues with subject headings, publishing, acquisitions, and racism emerged during the study and are covered in the discussion.